USING PODCAST TO IMPROVE STUDENTS’ LISTENING AND SPEAKING ACHIEVEMENTS - Utri Fitria; Machdalena Vianty; Ismail Petrus (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: This study aimed at investigating whether or not there were significant differences in English listening and speaking achievements between the twelfth grade students of MAN 3 Palembang who were taught by using Podcasts and those who were not, and this study aimed to get the students’ feedback about the use of Podcasts to improve their English listening and speaking achievements. There were 60 twelfth grade students of MAN 3 Palembang in the academic year 2014/2015 as the sample and they were divided into experimental (N= 30) and control groups (N= 30). Both groups were given pre- and post tests, but only the experimental group was given the treatment. To collect the data, listening and speaking tests were administered to students in both groups, and a questionnaire was administered to the students in the experimental group. The obtained data were analyzed by using paired and independent sample t-tests. The results showed that there were significant differences in both listening (mean difference= 23, p= 0.000) and speaking (mean difference= 17, p= 0.000) achievements between the experimental and control groups. Next, the results of questionnaire indicated that Podcasts served meaningful, appropriate, interesting tasks, activities and authentic materials which could attract the students’ attention, increase their motivation, and improve their comprehension. Hence, based on the results of this study, Podcast was an effective and innovative technology-based learning tool in English classroom, especially in integrating listening and speaking. Key words: Listening, speaking, Podcast, twelfth graders, technology-based learning